Charting a Course for the Future of Maine's Fisheries: An Interview with Commissioner Robin Alden - Alden, Robin (Maine Policy Review, 1996)
In a January, 1996 interview, Commissioner of the Maine Department of Marine Resources, Robin Alden shared her concerns about the direction of federal fisheries management and her goals for building a more dynamic and self-managing system here in Maine. In particular, Alden described the recent legislation which creates zone councils and an apprenticeship system in Maine’s lobster fishery. Alden articulated a direction for Maine’s fisheries that challenges conventional fisheries management and as such, is being watched closely by fisheries managers in Maine as well as elsewhere in the U.S. and overseas.
Keywords: Maine fisheries; fisheries management